Pengaruh Lingkungan Belajar dan Dukungan Teman Sebaya terhadap Hasil Belajar Mahasiswa - Indah Susanty; Marsofiyati Marsofiyati (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze the effect of learning environment and peer support on student learning outcomes in the Office Administration Education Study Program in 2022, Faculty of Economics, State University of Jakarta. this research is based on the importance of these factors in determining student learning outcomes. This research uses a quantitative approach with descriptive associative methods. The data were obtained by distributing questionnaires with a sample of 45 students as respondents and the data that had been obtained were then processed with data analysis techniques using SPSS. The results of this study indicate that the learning environment has a positive and significant influence on student learning outcomes with a coefficient value of 0.313 and p < 0.001. In addition, peer support also contributes significantly to student learning outcomes, with a coefficient of 0.486 and p < 0.001. The F-test showed that both variables simultaneously had a significant effect on student learning outcomes (F-count = 74.086, p < 0.001). The findings imply that creating a conducive learning environment and increasing support from peers can be effective strategies to improve student learning outcomes. This study is expected to be a reference for educators in designing more effective learning strategies.